DIRECTIONS OF INTRODUCTION OF “BENCHMARKING” SYSTEM IN EVALUATION OF EFFICIENCY OF MANAGEMENT ACCOUNTING SYSTEM IN THE ENTERPRISE - Fayzullayev Dilshod (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article discusses the most important factors for ensuring the competitiveness of enterprises in the market, the creation of effective tools for effective management accounting and control and internal audit of the enterprise management accounting system.